2018
DOI: 10.1055/s-0038-1636510
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovenous Anastomosis Bypass Surgery

Abstract: The field of lymphedema surgery has witnessed tremendous advancements over the years and has been coupled to the rapid growth of supermicrosurgical techniques. A lymphovenous bypass or lymphaticovenular anastomosis is a new technique that requires identification of patent, residual lymphatic channels and performing an anastomosis to a recipient venule, thereby allowing outflow of lymphatic fluid and improvement in a patient's lymphedema. This article provides a summary of the maturation of the technique, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Intraoperative ICG is used to identify potential lymphatic vessels for lymphatic‐venous bypass 36,37 …”
Section: Lymphatic Imagingmentioning
confidence: 99%
“…Intraoperative ICG is used to identify potential lymphatic vessels for lymphatic‐venous bypass 36,37 …”
Section: Lymphatic Imagingmentioning
confidence: 99%
“…In appropriately selected patients, LVAs have demonstrated objective and subjective improvements in most patients (Leung et al, 2015;Scaglioni et al, 2017). LVAs have promising potential and their reproducible results has led it to be considered one of the gold standard treatments for lymphoedema (Chang et al, 2018). Despite the significant improvements reported, LVAs do not cure lymphoedema, though patients who no longer suffer from swelling and do not need to wear compression garments may consider themselves cured.…”
Section: Figure 4 End To End Lymphaticovenous Anastomosismentioning
confidence: 99%
“…LVA allows obstructed lymphatic pathways to be bypassed by connecting superficial lymphatic vessels to nearby venules. 12 Increasing studies and reviews have shown the promise of LVA for extremity lymphedema, 13 but the literature remains new on systematic measures of both objective and subjective improvement following LVA for UE. Furthermore, little data exist on an optimal preoperative and perioperative treatment plan [eg, use of compression and/or splinting; use of indocyanine green (ICG)] to achieve satisfactory outcomes.…”
Section: Introductionmentioning
confidence: 99%